Rapport du dialogue sur l’engagement des étudiants et des futurs professionnels pour de meilleurs services de santé en français dans un contexte minoritaire - Bouchard, Pier; Vézina, Sylvain; Savoie, Mylène (Consortium national de formation en santé, 2010)

Socially responsible medical education: innovations and challenges in a minority setting - Schofield, Aurel; Bourgeois, Daniel (Medical Education, 2010)
Context Distributed medical education sites help train, recruit and retain doctors, notably in rural and isolated areas, by providing education and training in these areas and adapting their curriculum to meet the host community’s health needs. Objectives The Centre de Formation Médicale du Nouveau Brunswick (CFMNB; New Brunswick Medical Education Centre) was established by a partnership between two academic institutions, the Université de Sherbrooke (University of Sherbrooke), situated in the province of Quebec, and the Université de Moncton (University of Moncton), situated in the province of New Brunswick, in Canada. The CFMNB is specifically targeting a minority community (Acadians). Working to establish a high‐quality medical education programme, the CFMNB has also set community objectives to meet not only the health needs of this population, but also its social and economic needs. Methods This paper describes the overall objectives of this project, which are: to reduce the gap between community needs and academic institutional needs; to address ethno‐cultural and language differences in a defined minority population, and to develop collaboration between the partners involved, including government and community entities which are often perceived as operating in isolation from one another. We also describe why and how the CFMNB developed community‐focused objectives and the challenges that came with these innovations, and present lessons from the experience that may be relevant to other sites interested in the social responsibility of medical schools. Conclusions The CFMNB has produced interesting work and innovations in the field of social responsibility and has encountered many challenges. Continuing interaction between medical education, health research and health services to better address the needs of the population has been established. The information obtained by this process has been used to build a strategic plan for the CFMNB in order to ensure that it is socially responsive and has significant generalisable features.

Portrait de la santé et de l’état nutritionnel des aînés francophones à domicile au Nouveau-Brunswick - Villalon, Lita (Port Acadie, 2010)
Le Nouveau-Brunswick (N.-B.) possède une des plus vieilles populations du Canada. Selon Statistique Canada (2006), 14,7 pour cent de la population du N.-B. est âgée de 65 ans ou plus. La prévention constitue la solution idéale pour assurer le vieillissement en santé. Le but de l’étude était de faire le portrait de la santé et de l’état nutritionnel des aînés à domicile au N.-B. Les objectifs spécifiques étaient de déterminer 1) le profil socio-démographique, 2) le profil de santé, 3) la situation alimentaire et 4) l’état nutritionnel. Le Mini Nutritional Assessment (MNA) et des données alimentaires ont servi à l’évaluation de l’état nutritionnel. Près de 60 pour cent des sujets ne se conforment pas à la recommandation pour les groupes lait/produits laitiers, légumes/fruits et produits céréaliers du Guide alimentaire canadien. Les apports moyens en lipides, vitamine D, folates, calcium et zinc étaient insuffisants. Plus de 50 pour cent des sujets ne couvrent pas leurs besoins en plusieurs nutriments. Selon le MNA, 15 pour cent de sujets étaient à risque nutritionnel. Cinquante-quatre pour cent des hommes et 45 pour cent des femmes ont un poids santé. Des différences ont été observées selon l’identité linguistique, soit entre francophones et anglophones, et en fonction du sexe.